APLIKASI E-OPEN SEBAGAI WUJUD E-GOVERNMENT DALAM INOVASI PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DISDUKCAPIL KOTA BEKASI - Yussrul Hanna; Aufarul Marom; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2023)
Population Administration service and E-Government are important issues in Bekasi City. From the results of inspections in 2019, the Mayor of Bekasi City found that there was a very poor quality of service at the Bekasi City Population and Civil Registration Office (DISDUKAPIL). In following up on the Mayor's direction, DISDUKCAPIL Bekasi City created the E-Open application (Online Electronic Population Services). This study aims to determine the E-Open application process as a form of E-Government in the innovation of population administration services at DISDUKCAPIL of Bekasi City based on the theory of E-Government according to the results of a Harvard JFK School of Government study, namely support, capacity and value and identify supporting and inhibiting factors. The research method used in this study is descriptive qualitative using primary data sources obtained through in-depth interviews and observations in the field as well as secondary data. The results showed that the implementation of the E-Open application as a form of E-Government in the innovation of population administration services is still not optimal because there are obstacles in terms of human resources, namely the absence of experts (programmers) which has an impact on hampering the development and improvement of E-Open applications which are still often errors and cannot be accessed so that the public cannot take care of administrative files. The supporting factors in the E-Open application process as a form of E-Government are leadership, stakeholders and financial resources. While the inhibiting factors are human resources and technology & information.